Recurrence patterns and evolution of submicroscopic and asymptomatic Plasmodium vivax infections in malaria-endemic areas of the Peruvian Amazon - Garcia Castillo, Stefano S. (2024)
Funding agency: International Center of Excellence in Malaria Research (ICEMR). US Public Health Service, National Institutes of Health/National Institute of Allergy and Infectious Diseases (NIH/NIAID), USA (U19AI089681). Fogarty Training Grant (NIH-USA) (2D43TW007120-11A).